The benefit of bevacizumab therapy in patients with refractory vasogenic edema caused by brain metastasis from lung and colon cancers - Bai, Xuexue; Zhou, Meng (Frontiers in Oncology, 2022)
Objective This retrospective study investigated the efficacy of bevacizumab in refractory brain edema caused by brain metastasis from lung cancer and colon cancer. Methods A total of 72 patients with refractory brain edema were divided into the lung cancer and colon cancer groups according to their primary tumor. All patients received a single bevacizumab treatment for refractory brain edema. MRI was performed 1 week before the treatment and 4 weeks after the treatment. The edema and tumor volumes were calculated using imaging modalities. Results After a single bevacizumab treatment, the refractory brain edema of 61 patients was controlled, and the clinical symptoms of 65 patients were improved. The average edema volume before treatment was 201,708.97 ± 61,426.04 mm3, which has decreased to 116,947.01 ± 43,879.16 mm3 after treatment (P < 0.05). After treatment, the edema index decreased from 25.97 ± 7.15 to 17.32 ± 5.24 (P < 0.05).We found that brain edema was controlled in 40 patients (93.02%) in the lung cancer group and 21 patients (72.41%) in the colon cancer group (P<0.05). In addition, 22 patients (88.00%) in the radiotherapy group achieved edema control, compared to 39 (82.98%) in the non-radiotherapy group (P>0.05). Nine patients experienced hypertension after treatment, two patients exhibited decreased platelet counts, and no hemorrhage cases were observed. Conclusion Bevacizumab can significantly alleviate refractory brain edema, and there is a significant difference in the efficacy of bevacizumab on refractory brain edema caused by brain metastasis from lung and colon cancers.